Structure and properties of Bi(Zn½Ti½)O3‐modified Pb(Zr, Ti)O3 piezo‐/ferroelectric ceramics around the ternary morphotropic phase boundary. Issue 2 (24th September 2021) - Xie, Yujuan; Wang, Bi‐Xia; Claire, Neha; Ye, Zuo‐Guang
Abstract: To develop high‐performance piezo‐/ferroelectric materials, Bi(Zn½ Ti½ )O3 –PbZrO3 –PbTiO3 (BZT–PZ–PT) ternary solid solution with compositions around the morphotropic phase boundary (MPB) is synthesized by solid‐state reaction. The crystal structure and electric properties are investigated systematically by X‐ray powder diffraction (XRD), dielectric spectroscopy, and ferroelectric and piezoelectric measurements. On the basis of the results of the XRD, dielectric and ferroelectric measurements, the pseudo‐binary phase diagram of the y Bi(Zn½ Ti½ )O3 –(1 −  y )[(1 −  x )PbZrO3 – x PbTiO3 ] system has been constructed for three series, namely, y  = 0.05, 0.10, and 0.15. It is found that the introduction of BZT into the PZT system makes the paraelectric to ferroelectric phase transition more diffuse, brings the MPB to a lower PT content, and enlarges the MPB region. The best properties with an improved dielectric constant ε ' = 1248, and a large remnant polarization P r  = 33 μC/cm 2, as well as a relatively high T C  = 286°C, and a high coercive field E c  = 23 kV/cm was achieved in the y  = 0.15 series with MPB composition x  = 0.425, making it a promising material for high‐power piezoelectric applications.